Antimicrobial Activity of Polyphenols and Natural Polyphenolic Extracts on Clinical Isolates - Tamara Manso; Marta Lores; Trinidad de Miguel (MDPI AG, 2021)
Antibiotic resistance is a growing global problem that affects people, animals, the environment, and the economy. Many clinically relevant bacteria have become resistant to antibiotics, and this fact is emerging as one of the major threats to public health. The lack of new antibiotics, which is due to their time-consuming and costly development, exacerbates the problem. Therefore, it is necessary to identify new antimicrobial agents to treat bacterial and fungal infections. Plant extracts, which are valuable sources of bioactive compounds, mainly polyphenols, play an important role as a new strategy to combat pathogenic microorganisms. There is an extensive body of supporting evidence for the potent antibacterial and antifungal activities of polyphenols. Furthermore, some polyphenols show a synergistic effect when combined with antibiotics and antifungals, suggesting a promising alternative for therapeutic strategies against antibiotic resistance. However, only a few articles are found when searching the antibacterial or antifungal activities of polyphenols employing clinical isolates. Hence, this review focuses on the antimicrobial activity of polyphenols and extracts rich in polyphenols on clinical isolates, organized according to the World Health Organization priority pathogens classification.